2020
DOI: 10.3389/fpls.2020.00835
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Curtovirus V2 Protein, a Functional Homolog of Begomovirus V2

Abstract: Geminiviruses are single-stranded DNA plant viruses with circular genomes packaged within geminate particles. Among the Geminiviridae family, Begomovirus and Curtovirus comprise the two best characterized genera. Curtovirus and Old World begomovirus possess similar genome structures with six to seven open-reading frames (ORF). Among them, begomovirus and curtovirus V2 ORFs share the same location in the viral genome, encode proteins of similar size, but show extremely poor sequence homology between the genera.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 46 publications
0
26
1
Order By: Relevance
“…V2 is considered as the strongest PTGS suppressor encoded by begomoviruses (Luna et al, 2017). It may suppress PTGS by impairing the RDR6/SGS3 pathway (Luna et al, 2020). Although previous reports and our work all showed that the expression of V2 itself is sufficient to induce pathogenicity symptoms on host plants, this activity is independent of PTGS suppression function of V2 (Luna et al, 2020).…”
Section: Discussioncontrasting
confidence: 46%
“…V2 is considered as the strongest PTGS suppressor encoded by begomoviruses (Luna et al, 2017). It may suppress PTGS by impairing the RDR6/SGS3 pathway (Luna et al, 2020). Although previous reports and our work all showed that the expression of V2 itself is sufficient to induce pathogenicity symptoms on host plants, this activity is independent of PTGS suppression function of V2 (Luna et al, 2020).…”
Section: Discussioncontrasting
confidence: 46%
“…For example, the V2 protein of beet curly top virus (BCTV) can induce severe systemic necrosis in N. benthamiana plants, the C1 protein of apple geminivirus (AGV) can induce severe plant dwarfing symptoms, and the C4 protein of Malvastrum yellow vein virus (MaYVV) can induce N. benthamiana leaf upward rolling symptoms (Jing et al, 2019;Luna et al, 2020;Zhan et al, 2018). It is noteworthy that the AC5/C5 proteins of begomoviruses have different functions in virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…AV2 and V2 also suppress antiviral RNA silencing in the amplification phase and interfere with host methylation activities, downstream events of TGS [77][78][79]. TYLCV V2 interacts with and inhibits the suppressor of gene silencing 3 (SGS3), the cofactor of RDR6; thereby, affecting vsiRNA amplification [80].…”
Section: Geminiviral Suppressors Of Ptgs and Tgsmentioning
confidence: 99%
“…V2 may also sequester the RDR6/SGS3 intermediate/substrate dsRNA with 5' overhang ends from SGS3 association, further interfering with vsiRNA amplification [77,80]. Likewise, V2 from the curtovirus beet curly top virus (BCTV) has been recently shown to suppress post-transcriptional gene silencing (PTGS) by impairing the RDR6/SGS3 pathway [77,78]. CLCuMV V2 interacts with long dsRNA to prevent DCL processing, whereas tomato yellow leaf curl China virus (TYLCCV) V2 interacts with siRNAs to prevent AGO incorporation [70,81].…”
Section: Geminiviral Suppressors Of Ptgs and Tgsmentioning
confidence: 99%